The myth of choice in Maryam Lee’s unveiling choice - Natrah Noor,; Bahiyah Abdul Hamid,; Normalis Amzah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Malaysia has witnessed Islamic revivalism since the 1980s and its Islamisation is exemplified in the normalisation of hijab. Although the adoption of hijab is often cited as a choice in Malaysia, Maryam Lee’s controversial book Unveiling Choice presents an alternative portrait of choice in a society where hijab is a predominant practice. Using Wodak’s (Reisigl & Wodak, 2005, 2017; Wodak, 2001, 2018) Discourse Historical Approach (DHA) to Critical Discourse Studies (CDS), this paper explores the argumentation strategies used against women, particularly Maryam in challenging and delegitimising her de-hijabbing decision. The findings revealed how hijab is not only indoctrinated from childhood but the choice of removing it is delegitimised using linguistic means of topoi; more specifically topos of authority, threat and consequence. This paper concludes by highlighting the implication of these topoi to women’s agency pertaining to hijab in a society where the pressure to wear it is indoctrinated and forceful, resulting in hijab becoming a tool of hegemonic gendered practice that works toward sustaining the patriarchal status quo in Malaysia.